Itapuã and its Maritimities of Fishing and Shellmound Landscape, Vila Velha, Espírito Santo - Nogueira, Matheus Nascimento; Campos, Martha Machado (Farol, 2025)
This article investigates the coastal city's relationship with the sea; the maritime aspects of Itapuã (Vila Velha, Espírito Santo) and its artisanal fishing as an expression. It draws on historical documentation and records, as well as secondary sources, in addition to the theory of the topic. The singularities of Itapuã's maritime aspects are revealed as an indigenous maritime sociocultural phenomenon. It concludes that the maritime aspects of fishing in Itapuã are an important interpretive key to the town's relationship with the sea and its shellmound landscape.
Keywords: sea; maritime aspects; landscape